2015
DOI: 10.1016/j.compositesb.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical/experimental impact events on filament wound composite pressure vessel

Abstract: a b s t r a c tImpacts on pressure vessels, produced by winding glass fibre with vinyl ester resin over a polyethylene liner, were numerically and experimentally investigated in the current work.Pressure vessels were experimentally tested under low velocity impact loads. Different locations and incident energies were tested in order to evaluate the induced damage and the capability of the developed numerical model.An advanced 3-D FE model was used for simulating the impact events. It is based on the combined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In recent years most of research of impact resistance of composite structures made using filament winding has been concerned with low-velocity impacts [9,10]. Ballistic impact damage results presented in this paper cannot be compared to results from the literature concerning low-velocity impacts.…”
mentioning
confidence: 93%
“…In recent years most of research of impact resistance of composite structures made using filament winding has been concerned with low-velocity impacts [9,10]. Ballistic impact damage results presented in this paper cannot be compared to results from the literature concerning low-velocity impacts.…”
mentioning
confidence: 93%
“…Glass fiber reinforced epoxy (GF/epoxy) composite pressure vessel has been widely used in various fields due to the characteristics of high strength/stiffness‐to‐weight ratios and good fatigue resistance . Compared with the traditional metal pressure vessels, GF/epoxy composite pressure vessel is a new product, and they are made of high‐strength continuous fiber impregnated with polymer‐based resin, wound, and solidified on the liner .…”
Section: Introductionmentioning
confidence: 99%
“…The sliding was performed normal to the fibers' orientation. They demonstrate that the suggested micro/ macro FE approach adopted is more appropriate to predict the wear modes than the equivalent macro-mechanical approaches [9]. They studied the composite damage modes and showed that the high shear stress was in the origin of the matrix breaking with the appearance of thin films of wear debris.…”
Section: Introductionmentioning
confidence: 99%